Pemetaan bibliometrik dengan aplikasi Vosviewer terhadap perkembangan penelitian bidang pertanian di Indonesia - Yunus Winoto; Hawaari Ahmad Dimas (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
This study is aimed at mapping the development of agricultural research in Indonesia. The data collected by searching through Scopus database using agricultural and Indonesia keywords. Data was analyzed descriptively by year of publication, names and countries of institutions, journal names, authors’ productivity, and research subjects. To map the development of the research, data was exported to Comma Separated Values (CSV) format. The exported data was analyzed by using VOSViewer to figure out bibliometrical mapping of agricultural research in Indonesia. Results showed that the number of agricultural research indexed in Scopus during 1995 to 2015 was increasing significantly with the most number found in the Bulletin of Indonesian Economic Studies. The Agricultural Institute of Bogor has the most number of articles indexed in Scopus. The most productive foreign authors with the most number of articles on agricultural research in Indonesia is Tscharntke. Local authors with the most articles are Parikesit and Buchori. The most frequent countries involved in collaborative research on Indonesian agriculture are the US, Australia, and Japan. Agricultural and Biological Sciences are the most frequent subjects. Network visualization showed that the development of agricultural research in Indonesia can be grouped into three clusters: first cluster with 149 topics, second cluster with 105 topics, and third cluster with 48 topics.